Recruitment of new graduates of business related courses in to the banking industry - Montilla, Charo C.; Solmirano, Mark Anthony M.; Superticioso, Mary Rose D.; Tondo, Moises E. (2001)
As the number of new graduates of business related courses add by thousands each year in Iloilo City alone, only a few are absorbed or hired by one of the biggest industries in the city, which is most-likely to absorb these graduates, the banking sector. This study shows that the present status of new graduates as they enter the real world of labor supply in the banking industry. Reading on, the study will present its discovery on how hard it is to find a job, to compete with hundreds of other possible applicants just to qualify for a relatively small number of job opportunities in the banking industry in Iloilo City, among others. This study shows the factors that affected the current status of employment of this industry especially under the recent political and economic instability experienced by the country in addition to the effects of globalization and the age of automation or computerization, which the city is gradually being subjected to. The biggest factor that affected the reason why most of the banks did not hire was due to sufficiency of employees followed by the effects of economic crisis. Among those hired new graduates, majority has temporary employment status. This study also discloses information as to the factors considered why companies hire specific employees. It has tapped into the different qualification preferences considered by the banks with their newly hired, fresh graduates, employees. Among the attributes or qualifications, still, passing the companies own tests were the most preferred suitability of the degree finished to the job and and high grades and/or good working performance follows respectively. The study considered the banks in Iloilo City for its respondent's statistics on the new graduates or those who graduated from March 2000 to the present were also acquired from universities and colleges in Iloilo city. These were then compared and evaluated to arrive at the status of the employment of theses graduates by the banking industry.
[Research Paper] (BA 200 - Business Research) -- Iloilo City : UPV-CM, March, 2001.